2017
DOI: 10.1080/00140139.2017.1349937
|View full text |Cite
|
Sign up to set email alerts
|

Exploring mobility & workplace choice in a flexible office through post-occupancy evaluation

Abstract: Developments in information and communication systems, organisational structure and the nature of work have contributed to the restructuring of work environments. In these new types of work environments, employees do not have assigned workplaces. This arrangement helps organisations to minimise rent costs and increase employee interaction and knowledge exchange through mobility. This post-occupancy evaluation (POE) study focuses on a flexible office in a Gold Leadership in Energy and Environmental Design-certi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 40 publications
6
58
2
Order By: Relevance
“…However, an ABW environment seems to hamper workers' concentration and privacy (Engelen et al, 2018). Other studies have shown that satisfaction with ABW environments may differ strongly between and within organizations (Brunia, De Been, & Van der Voordt, 2016;Göçer, Göçer, Karahan, & Oygür, 2018;Hoendervanger, Ernst, Albers, Van Yperen, & Mobach, 2018;Leesman, 2017). In a number of field studies, satisfaction was below expectations, with concentration, privacy, and the loss of an assigned workstation listed as major self-reported issues (Babapour, 2019;Bodin Danielsson & Bodin, 2009;De Been & Beijer, 2014;Van der Voordt, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, an ABW environment seems to hamper workers' concentration and privacy (Engelen et al, 2018). Other studies have shown that satisfaction with ABW environments may differ strongly between and within organizations (Brunia, De Been, & Van der Voordt, 2016;Göçer, Göçer, Karahan, & Oygür, 2018;Hoendervanger, Ernst, Albers, Van Yperen, & Mobach, 2018;Leesman, 2017). In a number of field studies, satisfaction was below expectations, with concentration, privacy, and the loss of an assigned workstation listed as major self-reported issues (Babapour, 2019;Bodin Danielsson & Bodin, 2009;De Been & Beijer, 2014;Van der Voordt, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…• Visual comfort, access to daylight, and view [19][20][21]; • Noise distraction, lack of privacy, and communication [22][23][24][25][26][27]; • Office design [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The other dimension that has been studied was "ventilation rate" (i.e., supply of outdoor air) due to its indirect influence on workers' performance, caused by the impact of ventilation on thermal comfort, air quality, and concentration of indoor generated pollutants [40,41]. In addition, another key finding in fully air-conditioned open-plan offices is that occupants prefer to have a higher-degree of control over their immediate surroundings, including but not limited to thermostats, shading devices, and operable windows [27]. Interpersonal differences when it comes to occupants' thermal preferences have also been extensively documented [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Management often focuses on productivity, quality and economic profits, while work environment issues sometimes tend to be neglected. what is prioritized in terms of importance for increasing operational efficiency or issues related to safety in operations [17]. This is in contrast to several studies showing the relation between ergonomics, quality and productivity [12,13,14,42].…”
Section: Theoretical Backgroundmentioning
confidence: 91%